Techno-Economic Analysis of a Micro-Scale Off-Grid Solar Power Plant Using HOMER Software at the Operational Building - Sepannur Bandri; Zuriman Anthony; Fauzan Ismail; Taufal Hidayat; Sitti Amalia; Dwi Harinitha; Alfith Alfith (Jurnal Ilmiah Telsinas, 2026)
Rising electricity costs and fossil-fuel dependence in government facilities underscore the urgency of transitioning to renewable energy. This study determines the optimal configuration and economic feasibility of a micro-scale off-grid Solar Power Plant at the Operational Building of Balai Teknik Perkeretaapian (BTP) Kelas II Padang, supplied entirely by PLN grid tariff P1 (131,000 VA). A quantitative descriptive method combined five-day load measurement, manual calculation, and HOMER Pro simulation, using NASA POWER solar radiation data (annual average 4.62 kWh/m²/day). Manual calculation yielded 39.68 kW installed panel capacity, 339.97 kWh battery capacity (83 LiFePO4 units), and 80 kW inverter capacity; with a 10% Balance of System (BOS) allowance, Cost of Energy (COE) is IDR 1,429/kWh, 1.1% below the PLN tariff of IDR 1,444.70/kWh. HOMER Pro recommended 45.26 kW installed capacity with identical battery and inverter sizing, yielding COE of IDR 1,494/kWh with BOS, 3.4% above tariff, reversing the hardware-only comparison. Both configurations remain NPV-positive and PI above 1.0 within 25 years, but only the manual configuration is recommended as economically preferred. Sensitivity analysis identifies battery price and service life as the most critical risk factors. This study contributes measured load data with explicit BOS treatment, not previously applied to government railway facilities in Indonesia.